Effect of fruit size on the growth and development of andean blueberry (vaccinium meridionale swartz) seedlings from four locations in the colombian andes (2014)
Andean blueberry propagation is done with wild plants and there is an absence of knowledge for the agronomical potential of the available materials for sexual propagation. Therefore, developing a propagation protocol that provides technical information for field growers is needed. The present paper aimed to evaluate the effect of the size of the fruits that were used to extract the seeds on the growth and development of Andean blueberry plants during the germination and nursery stages, comparing fruits from four different regions of Colombia: Antioquia, Cauca, Cundinamarca and Boyaca. During the germination stage, seeds from Antioquia and Cauca showed the best results with germination rates close to 90% and reached important physiological events, such as seed coat cracking and radicle extension earlier than seeds from Boyaca and Cundinamarca. In the nursery stage, fruit size significantly affected the growth variables, such as plant height and leaf length, in all the different seed origins. Seedlings from Boyaca showed better results for growth and development after transplanting, as indicated by a higher amount of leaves and presence of basal branching, followed by seedlings from Cauca, Cundinamarca and Antioquia, which showed delayed phenological events.